2022
DOI: 10.31234/osf.io/b7f6k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Through the looking glass: the neural basis of self-concept in young adults with antisocial trajectories

Abstract: Self-concept is shaped by social experiences, but it is not yet well understood how the neural and behavioral development of self-concept is influenced by a history of antisocial behavior. In this pre-registered study, we examined neural responses to self-evaluations in young adults who engaged with antisocial behavior in childhood and either desisted or persisted in antisocial behavior. A self-concept task was performed by 94 young adults (age range 18–30-yrs). During the task, participants with a persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 54 publications
(98 reference statements)
0
10
0
Order By: Relevance
“…In line with this idea, recent studies have shown that life-course persistent antisocial behavior–but not desistant trajectories–was characterized by differential cortical and subcortical brain structure ( Carlisi et al, 2020 , 2021 ). However, until recently, possible functional mechanisms that help explain how and why differences between persistent and desistant antisocial developmental trajectories arise remained largely elusive, especially in young adulthood ( van de Groep et al, 2022a , b ). In the current review, we highlight and summarize recent functional neuroimaging studies on social-cognitive information processing (self- and other oriented) showing that, compared to desistant and non-antisocial behavior, persistent antisocial behavior in early adulthood is largely characterized by distinct difficulties in social cognitive functions and related disturbances in underlying brain functioning ( Brazil and Buades-Rotger, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In line with this idea, recent studies have shown that life-course persistent antisocial behavior–but not desistant trajectories–was characterized by differential cortical and subcortical brain structure ( Carlisi et al, 2020 , 2021 ). However, until recently, possible functional mechanisms that help explain how and why differences between persistent and desistant antisocial developmental trajectories arise remained largely elusive, especially in young adulthood ( van de Groep et al, 2022a , b ). In the current review, we highlight and summarize recent functional neuroimaging studies on social-cognitive information processing (self- and other oriented) showing that, compared to desistant and non-antisocial behavior, persistent antisocial behavior in early adulthood is largely characterized by distinct difficulties in social cognitive functions and related disturbances in underlying brain functioning ( Brazil and Buades-Rotger, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal research generally supports the taxonomy, but additional developmental trajectories have also been identified ( Piquero, 2008 ). One such trajectory consists of individuals with childhood-limited of antisocial behavior who show conduct problems early in life, but desist in adolescence and early adulthood ( Monahan et al, 2013 ; Bevilacqua et al, 2018 ; van de Groep et al, 2022a , b ). Whether antisocial behavior is present and persistent can be measured and operationalized in different ways, with two common approaches involving classification based on clinical, psychiatric diagnoses and symptoms, and classification based on offending patterns based on police registrations ( Bersani and Doherty, 2018 ; Moffitt, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations